2009
DOI: 10.1107/s1600536809036794
|View full text |Cite
|
Sign up to set email alerts
|

Trineodymium(III) pentairon(III) dodecaoxide, Nd3Fe5O12

Abstract: Key indicators: single-crystal synchrotron study; T = 298 K; mean (Fe-O) = 0.0001 Å; R factor = 0.016; wR factor = 0.018; data-to-parameter ratio = 50.4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It has been reported that Fratello et al have synthesized successfully praseodymium and neodymium iron garnets by liquid phase epitaxy (LPE) on Sm 3 (ScGa) 5 O 12 substrates at about 875 and 900 1C [19,20]. By synchrotron radiation study, Komori recently determined the crystal structures of the above synthesized compounds [21,22]. In LPE process, perovskite orthoferrite as a primary phase grows on the substrate, the lattice constants of samples and substrates need to match exactly, and the impurities of Pb and Pt could be embedded in the sites of the lattices.…”
Section: Introductionmentioning
confidence: 96%
“…It has been reported that Fratello et al have synthesized successfully praseodymium and neodymium iron garnets by liquid phase epitaxy (LPE) on Sm 3 (ScGa) 5 O 12 substrates at about 875 and 900 1C [19,20]. By synchrotron radiation study, Komori recently determined the crystal structures of the above synthesized compounds [21,22]. In LPE process, perovskite orthoferrite as a primary phase grows on the substrate, the lattice constants of samples and substrates need to match exactly, and the impurities of Pb and Pt could be embedded in the sites of the lattices.…”
Section: Introductionmentioning
confidence: 96%
“…Fratello et al [23] successfully synthesized neodymium iron garnets by liquid phase epitaxy (LPE) at about 1173 K. They obtained films of Nd with the following characteristics YIG with a lattice parameter of 12.596 Å, Curie temperature of 567 K and a saturation magnetization of around 30 emu/g at room temperature. Komori et al [24] synthesized the single crystals of neodymium iron garnet by low-temperature liquid phase epitaxy on Sm 3 (ScGa) 5 O 12 and described the crystal structure garnet, in which the Nd 3+ substituent cations were coordinated by eight oxygen atoms in distorted dodecahedrons. Arun et al [25] studied the synthesis of Nd x Y 3− x Fe 5 O 12 by the sol–gel auto-combustion method.…”
Section: Introductionmentioning
confidence: 99%
“…165 HoIG is a member of the isostructural garnet family and its general formula is Z 3 X 2 Y 3 O 12 , where the Z cations occupy the dodecahedral sites, the X cations occupy the octahedral sites and the Y cations occupy tetrahedral sites in the crystal structure, as shown in Figure S1 (Supporting Information). In the case of HoIG, Ho 3+ occupies the dodecahedral sites and Fe 3+ occupies both the octahedral and tetrahedral sites in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structure (cubic, Ia 3 d ) of garnet calculated using the crystallographic data in ref , Digital image of 33% (w/w) HoIG/PAN electrospun fiber mat; FTIR spectra of PAN, 165 HoIG/PAN fiber and 165 HoIG powder; PXRD pattern of 165 HoIG powder and electrospun fibers with 33% (w/w) 165 HoIG; diagrams showing homogeneity of 33% (w/w) 166 Ho-containing electrospun polymer nanofibrous mats; 33% (w/w) 166 Ho-containing electrospun PAN mats before (control) and after neutron-activation for 0.5, 1.0, 2.0 and 4.0 h in a thermal neutron flux of approximately 3.5 × 10 12 n/cm 2 ·s in a 1 MW nuclear reactor; SEM images and fiber diameter distributions of 50% (w/w) HoIG-loaded bandages before and after neutron-activation for 0.5, 1.0, 2.0 and 4.0 h (using 25 images), SEM images and fiber diameter distributions of PAN bandages before heated and after heated at 100, 150 and 200 °C; TGA and DTA curve of electrospun PAN fibers. This material is available free of charge via the Internet at .…”
mentioning
confidence: 99%